Additions and emendations to the annotated checklist of anthiadine fishes (Percoidei: Serranidae) - Anderson, William D. Jr. (Zootaxa, 2022)
Anderson (2018) published an annotated checklist of anthiadine fishes with information on the 29 genera and 226 species then considered valid. Since then there have been a number of publications on the systematics of anthiadines, including descriptions of 23 new species and one new genus. Herein, data on those new taxa and emended accounts of others are presented.